Efektifitas Pelayanan Kartu Keluarga (KK) Dan Surat Pindah Pada Tahun 2020 di Kecamatan Wlingi Kabupaten Blitar - Sutowo; Amira Rizki (Universitas Islam Balitar, 2021)
Reformation in public services is currently needed in order to realize a community service system at the Wlingi sub-district office in Blitar Regency for the community, efforts should be made to improve services that are fast, precise and accurate both directly and indirectly in order to create good service and provide satisfaction to the community. The effectiveness of the Family Card and the Letter moved is very much needed in determining the assessment of community satisfaction with the services carried out by the Wlingi District Office. The research method used is a descriptive qualitative research method, namely (1) Research Design (2) Researched Objects (3) Data Sources (4) Collection Techniques Data (5) Data Analysis Techniques and Data Validity. The results of the effectiveness of the researchers obtained from six objects in which the researchers carefully obtained results as much as 96% of the people understood and learned about the servants' productions carried out by Wlingi Subdistrict, 96% of the people stated that the Family and Letter Card completion times moved very quickly in minutes , 93% of the people stated that the cost of service in Wlingi District was gone (free), 60% of the people stated that the Family Card and Moving Mail service products were very durable and inefficient to carry around, 53% of the community was comfortable with facilities and infrastructure in the Wlingi District service, and 76% of the community were satisfied with the competency of the service provider who was fast, precise, capable, and friendly. From the results of the effectiveness of the services that the researchers describe, there is a problems that can hamper the effectiveness of services in the Wlingi District Office.